Five-frequency Galileo long-baseline ambiguity resolution with multipath mitigation - Wang, Kan; Khodabandeh, Amir; Teunissen, Peter (Springer, 2018)
© 2018, The Author(s). For long-baseline over several hundreds of kilometers, the ionospheric delays that cannot be fully removed by differencing observations between receivers hampers rapid ambiguity resolution. Compared with forming ionospheric-free linear combination using dual- or triple-frequency observations, estimating ionospheric delays using uncombined observations keeps all the information of the observations and allows extension of the strategy to any number of frequencies. As the number of frequencies has increased for the various GNSSs, it is possible to study long-baseline ambiguity resolution performance using up to five frequencies with uncombined observations. We make use of real Galileo observations on five frequencies with a sampling interval of 1 s. Two long baselines continuously receiving signals from six Galileo satellites during corresponding test time intervals were processed to study the formal and empirical ambiguity success rates in case of full ambiguity resolution (FAR). The multipath effects are mitigated using the measuremen ts of another day when the constellation repeats. Compared to the results using multipath-uncorrected Galileo observations, it is found that the multipath mitigation plays an important role in improving the empirical ambiguity success rates. A high number of frequencies are also found to be helpful to achieve high ambiguity success rate within a short time. Using multipath-uncorrected observations on two, three, four and five frequencies, the mean empirical success rates are found to be about 73, 88, 91, and 95% at 10 s, respectively, while the values are increased to higher than 86, 95, 98, and 99% after mitigating the multipath effects.